Diagnosis and surgical treatment of tumor-induced osteomalacia-a literature review and a case report - Peikai Huang; Mengqiang Xiao; Meng Zhang; Jun Chen; Jingzhi Ye; Meiyi Zhao; Jiahui Tang (SpringerOpen, 2022)
Abstract Background Tumor-induced osteomalacia (TIO) is a rare condition with fewer than 500 cases reported in the literature although described. Phosphaturic mesenchymal tumor (PMT) is often unrecognized cause of hypophosphatemia. This case report aims to highlight such a rare association which warrants clinical and radiologist attention. Case A 51-year-old man had pain in his feet 2 years prior to the most recent presentation in our clinic. The patient experienced increasingly severe body aches and pain, which affected the feet, hips, knees, ribs, waist, and shoulders. MRI and CT led to the diagnosis of multiple insufficiency fractures. Laboratory tests showed that inorganic phosphate (IP) levels had decreased to 0.52 mmol/L(0.81-1.45 mmol/L), while alkaline phosphatase (ALP) had increased to 216 U/L(38.0-126.0 U/L). Positron emission tomography computed tomography showed tumor-derived hypophosphate osteomalacia of the right iliac wing; surgical resection was performed. markers of bone metabolism and bone density returned normal postoperative, after 9 months follow-up. Conclusion The possibility of tumor-induced osteomalacia should be considered if unexplained joint pain, decreased bone mineral density, increased ALP and insufficiency fractures, and no similar family history are found in adult patients. Surgical resection of the tumor is the key to the treatment.